Smaller aortic dimensions do not fully account for the greater pulse pressure in elderly female hypertensives - Dart, A.; Kingwell, B.; Gatzka, C.; Willson, K.; Liang, Y.; Berry, K.; Wing, L.; Reid, Christopher; Ryan, P.; Beilin, L.; Jennings, G.; Johnston, C.; et al. (American Heart Association, 2008)
This study examined the importance of aortic dimensions in determining pulse pressure in elderly hypertensives participating in the 2nd Australian National Blood Pressure Study, including a substantial number not previously receiving blood pressure lowering medication. Aortic dimensions were determined by ultrasound at the transverse arch and at the insertion of the aortic valve. Unadjusted data showed negative (P<0.001) correlations between central (carotid) and (brachial) peripheral pulse pressure and both arch (-0.200, -0.181) and outflow tract (-0.238, -0.238) diameters. Correlations were similar in those previously treated with blood pressure lowering medication and in the treatment naïve. Central pulse pressure (84±26 versus 75±28 mm Hg, P<0.001) was higher and aortic dimensions (transverse arch 2.56±0.31 versus 2.88±0.35 mm, P<0.001) smaller in women than men. Women had greater aortic stiffness (beta index 29.4±36.1 versus 22.1±21.3, P<0.03). Other bivariate correlates of central pulse pressure were age, mean arterial pressure, height, heart rate, augmentation index, aortic stiffness (all P<0.001), and weight (P=0.027). In multivariate analyses gender remained a predictor of central pulse pressure (P<0.001) even with inclusion of aortic dimensions (P=0.013) height and weight. Other significant terms were age, heart rate, mean blood pressure, and aortic stiffness (all P<0.001). These findings demonstrate an independent inverse relation between aortic size and pulse pressure in older hypertensive subjects. Differences in aortic dimensions and stiffness between genders do not fully account for the observed blood pressure differences, suggesting that a contributory factor to gender differences in pulse pressure is an increased age-related mismatch in ventricular function and aortic stiffness in women compared with men. © 2008 American Heart Association, Inc.